Italian Recommendations for Placental Transfusion Strategies - Ghirardello, Stefano; Di Tommaso, Mariarosaria; Fiocchi, Stefano; Locatelli, Anna; Perrone, Barbara; Pratesi, Simone; Saracco, Paola (Frontiers in Pediatrics, 2018)
At delivery, if the cord is not clamped, blood continues to pass from the placenta to the newborn during the first minutes of life, allowing the transfer of 25-35 ml/kg of placental blood to the newborn, depending on gestational age, the timing of cord clamping, the position of the infant at birth, the onset of respiration, and administration of uterotonics to the mother. However, resulting benefits from delayed cord clamping (DCC) are not merely related to placental-to-fetal blood transfusion; establishing spontaneous ventilation before cutting the cord improves venous return to the right heart and pulmonary blood flow, protecting the newborn from the transient low cardiac output and systemic arterial pressure fluctuations. Recent meta-analyses showed that DCC reduces mortality and red blood cell transfusions in preterm newborns and increases iron stores in term newborns. Various authors suggested cord milking (UCM) as a safe alternative when DCC is not feasible. Many scientific societies recommend 30-60 seconds of DCC for both term and preterm newborns not requiring resuscitation. To improve the uptake of placental transfusion strategies, in 2016 an Italian Task Force for the Management of Umbilical Cord Clamping draft national recommendations for the management of cord clamping in term and preterm newborns. The task force performed a detailed review of the literature using the GRADE methodological approach. The document analyzed all clinical scenarios that operators could deal with in the delivery room, including cord blood gas analysis during DCC and time to cord clamping in the case of umbilical cord blood banking. The panel intended to promote a more physiological and individualized approach to cord clamping, specifically for the most preterm newborn. A feasible option to implement DCC in very preterm deliveries is to move the neonatologist to the mother’s bedside to assess the newborn’s clinical condition at birth. This option could safely guarantee the first steps of stabilization before clamping the cord and allow DCC in the first 30 seconds of life, without delaying resuscitation. Contra-indications to DCC and UCM are clinical situations that may endanger mother ‘s health and those that may delay immediate newborn’s resuscitation when required.